2012
DOI: 10.3324/haematol.2012.065714
|View full text |Cite
|
Sign up to set email alerts
|

Allogeneic stem cell transplantation for advanced acute promyelocytic leukemia in the ATRA and ATO era

Abstract: The role of allogeneic stem cell transplant in advanced acute promyelocytic leukemia patients who received standard first and second-line therapy is still unknown. We report the outcome of 31 acute promyelocytic leukemia patients (median age 39) who underwent allogeneic transplant in second-remission (15patients) or beyond (16patients. Sixteen patients were RT-PCR positive and 15 negative for PML/RARA pre-transplant. The 4-year overall-survival was 62 % and 31% for patients transplanted in second-remission and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 16 publications
1
18
0
Order By: Relevance
“…Several studies have identified prognostic factors in patients with relapsed APL who underwent salvage therapy with or without HSCT (Roman et al , ; Ramadan et al , ; Chakrabarty et al , ; Lou et al , ; Marjerrison et al , ; Lengfelder et al , ). However, most studies involved adults with very few subjects being <18 years of age (Chakrabarty et al , ; Marjerrison et al , ; Lengfelder et al , ).…”
Section: Refractory Aplmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have identified prognostic factors in patients with relapsed APL who underwent salvage therapy with or without HSCT (Roman et al , ; Ramadan et al , ; Chakrabarty et al , ; Lou et al , ; Marjerrison et al , ; Lengfelder et al , ). However, most studies involved adults with very few subjects being <18 years of age (Chakrabarty et al , ; Marjerrison et al , ; Lengfelder et al , ).…”
Section: Refractory Aplmentioning
confidence: 99%
“…Molecular CR at the time of transplantation has been shown to be an important prognostic factor. Ramadan et al () reported a significant difference in the 4‐year OS between patients transplanted in molecular CR and those with positive RT‐PCR at the time of allo‐HSCT (64% and 27%, respectively). Another study demonstrated that continued RT‐PCR positivity after HSCT predicts subsequent relapse (Roman et al , ).…”
Section: Refractory Aplmentioning
confidence: 99%
“…The BM chimerism showed good donor cell engraftment from the CBT with residual leukemia and recipient's cells, ensuring the presence of functional donor‐derived antigen‐presenting cells to favor a better GVL response. Considering that APL is a well‐known target for GVL with easy and sensitive determination of minimal residual disease, and the fact that this patient had limited disease burden at the second relapse, which happened late post‐CBT (28 months), we have decided to perform a BMT from the same donor. The BMT graft would favor engraftment due to higher stem cell dose, allowing the TBI‐containing full‐myeloablative conditioning regimen.…”
Section: Discussionmentioning
confidence: 99%
“…Once considered fatal, relapsed APL, which occurs in 15–25% of the cases, has been successfully treated with chemotherapy only , autologous or allogeneic HSCT , with the standard of care still controversial. More recently, a few publications have suggested that HSCT may be a more effective consolidation for refractory or relapsed APL .…”
mentioning
confidence: 99%
“…A study by Thirugnanam et al 49 showed a higher 5-year efs rate in patients treated with autologous hsct than in those receiving only ato with or without atra (83.33% vs. 34.45%, p = 0.001). Ramadan et al 46 examined the role of allogeneic hsct in second remission and beyond, reporting a 4-year os rate of 62% when hsct was performed in the second cr and 31% in patients transplanted beyond the second cr (p = 0.05). A study by Linker et al showed a 5-year disease-free survival rate of 67% after a median follow-up of 8.2 years in patients receiving two-step autologous hsct 50 .…”
Section: Questionmentioning
confidence: 99%